Leadless cardiac ventricular pacing using helix fixation: Step‐by‐step guide to implantation. (29th December 2022) - Laczay, Balint; Aguilera, Jose; Cantillon, Daniel J.
Abstract: Introduction: Leadless cardiac pacemakers are an alternative modality to traditional transvenous pacemaker systems. Recently receiving Food and Drug Administration approval, the AVEIR VR leadless pacemaker system provides a helix based active fixation leadless pacemaker system. This step‐by‐step review will cover patient selection, preprocedural planning, device implantation technique, implant site evaluation, troubleshooting, short‐ and long‐term complications as well as future directions for leadless pacing. Methods: We collected and reviewed cases from primary operators to provide a step‐by‐step review for implanters. Results: Our paper provides a guide to patient selection, pre‐procedural planning, device im plantation technique, implant site evaluation, troubleshooting, short‐ and long‐term complications as well as future directions for leadless pacing. Conclusion: The helix based active fixation leadless pacemaker system is a safe and efficacious way to provide pacing support to patients and provides an alternative to transvenous pacing systems. Our review provides a step‐by‐step guide to implantation.